Kejadian Luar Biasa Gondongan di SD Islam X Samarinda, 2024 - Riyanto, Rudy Agus; Pakki, Irfansyah Baharuddin; Sabena, Mela; Pasiakan, Meli; Erlina, Erlina; Andriani, Rima (Jurnal Epidemiologi Kesehatan Indonesia, 2025)
Mumps outbreaks are a public health issue that still frequently occur in elementary school settings, particularly among children with low immunization coverage. Therefore, a comprehensive epidemiological understanding is needed as a basis for control. This research aims to describe the epidemiological picture and causative factors of the mumps outbreak that occurred at Islamic Elementary School X in Samarinda City in 2024, using a case series design. The outbreak occurred from April to October 2024, while epidemiological data collection and case verification were conducted from December 2nd to 8th, 2024. The analysis uses surveillance data, field observations, and questionnaires administered to parents and teachers A total of 33 confirmed cases of mumps were reported from 291 students during the observation period, with an attack rate of 11.33%. The dominant symptoms found included parotid gland swelling (100%), fever (78.8%), headache (63.6%), and malaise (42.4%). The main risk factors include low MMR immunization coverage (54.5%), close contact between students in classrooms and extracurricular activities, and a lack of public understanding about preventing infectious diseases. The control efforts undertaken include case isolation, classroom disinfection, personal hygiene education, and cross-sector coordination with the Samarinda City Health Office, increased vaccination coverage, and school health education to prevent future outbreaks of mumps, thru additional MMR vaccinations for students who have not completed their doses, monitoring immunization status at the beginning of each school year, and improving personal hygiene education in schools. Keywords : Mumps, outbreak, epidemiology, primary school, vaccination